Die anerkennung von immaterialguterrechten in der Sharia - Abdul Ghani Azmi, Ida Madieha (VCH Verlagsgessellschaft, 1997)
This article is a shortened version of the author's doctoral thesis which was published under the title, "Gesetze zum Immaterialgu?terrecht und Islam in Malaysia," September 1995. It was written during a study visit at the Max Planck Institute in Munich, Germany.